SINKRONISASI PERATURAN PEMERINTAH PUSAT DAN PEMERINTAH DAERAH MENGENAI PENGENDALIAN BANJIR DI JAKARTA - Sania Maulida; Myrna A. Safitri; Endra Wijaya (Jurnal Manajemen Bencana (JMB), 2022)
The floods that occurred in several areas of the Special Capital Region of Jakarta Province are influenced by natural and unnatural factors, such as problem in spatial planning and its regulation in legal documents. This study discusses about synchronization problem between several regulations at national and regional level, namely Presidential Regulation Number 60 of 2020 and Regional Regulation of the Special Capital Region of Jakarta Province Number 1 of 2014. This study uses normative legal research method with statute and conceptual approach. The conclusion of this study is that there is still no regulation synchronization at the level of national and regional related to the floods control management. At the national level, Presidential Regulation Number 60 of 2020 already regulated in detail about floods control management through the spatial planning general policy, strategy of implementation, spatial system and structure, and direction of zoning regulation for Jakarta, Bogor, Depok, Tangerang, Bekasi, Puncak, and Cianjur regions. Different from that national level regulation, at the regional level, Regional Regulation of the Special Capital Region of Jakarta Province Number 1 of 2014, related to the floods control management, only focus on how to normalize the river as a part of drainage system in every district in Jakarta Province.